The Influence of E-WOM and Product Quality on Purchase Intention Mediated by Brand Image - Tiara Setianti; Liem Bambang Sugiyanto (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The skincare industry in Indonesia has grown rapidly due to increasing awareness of skin health and the influence of social media. However, variations in consumer experiences and online reviews often result in a misalignment between brand image and purchase intention, including for the local skincare brand Wardah. This study aims to examine the effect of Electronic Word of Mouth (E-WOM) and Product Quality on Purchase Intention, with Brand Image as a mediating variable. A quantitative approach was employed using a structured online survey, and the data were analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that E-WOM and Product Quality positively influence Brand Image. Brand Image also has a positive impact on Purchase Intention. Furthermore, E-WOM and Product Quality positively affect Purchase Intention both directly and indirectly through Brand Image. These findings highlight that consumer reviews and product quality serve as strategic drivers in shaping brand image and enhancing the purchase intentions of Wardah skincare consumers in Indonesia.